Advantages And Disadvantages of Digital Technologies in Language Teaching - X.T.Turayeva; M.A.Kholmurodova (Genius Journals, 2022)
This article deals with the beginning of digital literacy programs in the education curriculums, especially as they are mostly having effects on language teaching. The main purpose of this research is to talk about the benefits and barriers of utilizing technologies as teaching methods. The article concludes with the suggestions for educational research that the need of digital literacies in academic purposes.
Keywords: digital literacy; benefits; barriers; EFL classes